Weather patterns at Ruhija, Bwindi impenetrable national park, south west Uganda - Bitariho, Robert; Dennis, Babaasa; Aventino, Kasangaki (My University, 2000)
This report describes the weather patterns of Bwindi Impenetrable National Park using data collected at ITFC from Ruhija. Two climatic parameters were used to describe the weather patterns at Ruhija and these are rainfall and temperature. The two have been chosen because they have profound influence on the distribution of plants and animals and can easily be interpreted. We used the conventional rain gauge and the maximum-minimum thermometer to measure the two climatic parameters over a 13-year period (1987-1999). There are two rainfall peaks (March-May and September-November) and two dry season troughs (December-January and June July). The two main wet and dry seasons at Ruhija have been constant over years (at least from 1963-1999). During the 1987-1999 study period, the wettest year was 1988 and 1999 was the driest. The study shows that there has been a temperature increase since 1983. This was based from the data collected since 1987 to-date and compared with the available climate data from Butynski (1984) and the meteorological data of Kabale since 1918. According to this study, Ruhija has a mean daily maximum of 190C and a mean daily minimum of 140C. Mean annual temperature is 16.30C. These contrasts with the 1963-1987 data for which the mean daily maximum was 200C and mean daily minimum 70C, and a mean annual temperature of 130C. This study further shows that June and July are the coldest months while September and March are warmest. The two coldest and warmest periods correspond to the two dry season troughs and rainy season peaks respectively.